Implementing Task-Based Learning Strategy during the COVID-19 for Teaching English for Adult Learners - Muhammad Mugni Assapari (Universitas Ahmad Dahlan, 2020)
The purpose of this study is to find out the improvement of English learning results of Mataram State Islamic University students majoring in Da'kwah management and Communication by utilizing task-based learning strategies during covid-19. This study is a type of class action study with research subjects a student’s second semester of Da’kwah Fakulty. Data collection by way of in-depth interviews and direct observations. The research method used in research is qualitative descriptive. This research data includes the results of the study results and student responses regarding the utilization of task-based learning strategies. Techniques data collection of student learning results is carried out through tests in the form of test questions Objective. The data is descriptively analyzed using percentages. Analysis of learning process data obtained from observation data, and interviews are conducted qualitatively. The results showed there was a significant improvement in students' English speaking skills after taking part in online assignment-based learning. This proves that task-based English learning is effective in improving students' English speaking skills.